2022
DOI: 10.1111/cns.13837
|View full text |Cite
|
Sign up to set email alerts
|

Fine particulate matter exposure aggravates ischemic injury via NLRP3 inflammasome activation and pyroptosis

Abstract: Aims Accumulating evidence has suggested that airborne fine particulate matter (PM2.5) exposure is associated with an increased risk of ischemic stroke. However, the underlying mechanisms have not been fully elucidated. In this study, we aim to investigate the role and mechanisms of NLRP3 inflammasome and pyroptosis in ischemic stroke after PM2.5 exposure. Methods The BV‐2 and HMC‐3 microglial cell lines were established and subjected to oxygen–glucose deprivation and reoxygenation (OGD/R) with or without PM2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 67 publications
(118 reference statements)
2
8
0
Order By: Relevance
“…Compared to the previous studies showing that ROS generated by ZnO nanoparticles would activate NF-κB-mediated NLRP3 inflammasomes in A549 cells, the pyroptosis induced by FPM appeared to be attributed to the metal ion release. In addition, the activation of NLRP3 and the consequent cellular pyroptosis following FPM exposure have been observed both in vitro (such as BV-2 and HMC-3 microglial cell lines) and in vivo . …”
Section: Major Cell Death Pathways Induced By Fine Particulate Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the previous studies showing that ROS generated by ZnO nanoparticles would activate NF-κB-mediated NLRP3 inflammasomes in A549 cells, the pyroptosis induced by FPM appeared to be attributed to the metal ion release. In addition, the activation of NLRP3 and the consequent cellular pyroptosis following FPM exposure have been observed both in vitro (such as BV-2 and HMC-3 microglial cell lines) and in vivo . …”
Section: Major Cell Death Pathways Induced By Fine Particulate Mattermentioning
confidence: 99%
“…In addition, the activation of NLRP3 and the consequent cellular pyroptosis following FPM exposure have been observed both in vitro (such as BV-2 and HMC-3 microglial cell lines) and in vivo . 71 73 …”
Section: Major Cell Death Pathways Induced By Fine Particulate Mattermentioning
confidence: 99%
“…These inflammatory mediators become the external stimulus transduction signals required for the activation of the nuclear factor-κB pathway, which further activates the nuclear factor-κB signaling pathway, induces an inflammatory cascade, and aggravates neuroinflammation (Zhang Y. et al, 2018 ). PM 2.5 exposure can also activates the NLRP3 inflammasome, induces increased production of IL-1β and IL-18, causes systemic and neuroinflammation, and leads to endothelial and target organ damage (Gao et al, 2022 ).…”
Section: Underlying Mechanisms Of Brain Injurymentioning
confidence: 99%
“…The population survey data have shown that short-term and long-term exposure to PM 2.5 augments the risks of stroke incidence and mortality (Shah et al, 2015;Qiu et al, 2017). Experimental data have documented that in ammation and arteriosclerosis are the vital regulatory mechanisms that PM 2.5 exposure triggers stroke (Gao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%